Development of an occupational airborne chemical exposure matrix. (11th April 2016) - Sadhra, S. S.; Kurmi, O. P.; Chambers, H.; Lam, K. B. H.; Fishwick, D.; ,
Abstract : Background: Population-based studies of the occupational contribution to chronic obstructive pulmonary disease generally rely on self-reported exposures to vapours, gases, dusts and fumes (VGDF), which are susceptible to misclassification. Aims: To develop an airborne chemical job exposure matrix (ACE JEM) for use with the UK Standard Occupational Classification (SOC 2000) system. Methods: We developed the ACE JEM in stages: (i) agreement of definitions, (ii) a binary assignation of exposed/not exposed to VGDF, fibres or mists (VGDFFiM), for each of the individual 353 SOC codes and (iii) assignation of levels of exposure (L; low, medium and high) and (iv) the proportion of workers (P) likely to be exposed in each code. We then expanded the estimated exposures to include biological dusts, mineral dusts, metals, diesel fumes and asthmagens. Results: We assigned 186 (53%) of all SOC codes as exposed to at least one category of VGDFFiM, with 23% assigned as having medium or high exposure. We assigned over 68% of all codes as not being exposed to fibres, gases or mists. The most common exposure was to dusts (22% of codes with >50% exposed); 12% of codes were assigned exposure to fibres. We assigned higher percentages of the codes as exposed to diesel fumes (14%) compared with metals (8%). Conclusions: We developed an expert-derived JEM, using a strict set of a priori defined rules. The ACE JEM could also be applied to studies to assess risks of diseases where the main route of occupational exposure is via inhalation.